Classification of figures in primary school based on van Hiele’s model: Report of two cases - De León-Zamora, Wendy Loraine; Juárez-López, José Antonio; Juárez-Ruiz, Estela de Lourdes (Unnes Journal of Mathematics Education, 2023)
In this paper, the results of an investigation based on an activity on the recognition of geometric shapes are reported, where different figures were presented that must be classified in order to identify the level of reasoning of each student. The present investigation follows a qualitative method and the data collection was carried out through clinical interviews applied to two children, an 8-year-old boy and a 10-year-old girl, who at that time were in the third and fourth grades of primary school respectively, in the State of Puebla, Mexico. Among the main results, it stands out that both children were located at level 0 of reasoning according to van Hiele's classification, since they recognize geometric shapes by their physical appearance, not by their properties and relationships.